Associação entre perfil hemodinâmico de pacientes admitidos por insuficiência cardíaca descompensada e mortalidade - André Silva Rodrigues (2023)
Introduction: Heart failure is a very prevalent disease with high morbidity and mortality in our midst. It is the main cause of hospital admissions for cardiovascular disease in Brazil and its clinical presentation is related to the prognosis of the disease.Knowledge of this scenario is necessary to improve management strategies. Objectives: To describe the characteristics of hospitalizations for acute heart failure in Brazil and the association between the hemodynamic profile of hospital admission, based on congestion (wet or dry) and perfusion (cold or warm), with mortality outcomes, length of stay and rate of rehospitalization. Methods: National cohort of 2762 patients hospitalized for acute heart failure in Brazilian tertiary public hospitals, participants in the “Boas Práticas em Cardiologia” program, from March 2016 to December 2019, with a six-month follow-up. Analysis of population characteristics and hemodynamic profile at admission were performed, in addition to survival analyzes using COX models, for the association between the admission profile and mortality, and Logistic Regression for the chance of readmission. Results: The majority of this population is male (58.3%) and was admitted in a hot and humid profile (72.5%). The mean age was 60.2 years (±14.8) and the mean left ventricular ejection fraction on echocardiography was 39.8% (±17.3). Hospital mortality due to acute heart failure was 11.1% and the rehospitalization rate was 22%. There was an association between the cold clinical profiles and in-hospital mortality (HR=1.72; CI 1.27-2.31; p < 0.001) and between the wet profiles and the chance of readmission at 6 months (OR 2, 30; CI 1.45-3.65; p < 0.001). Conclusions: Acute heart failure in Brazil is responsible for high mortality and the hemodynamic profile of patients on hospital admission correlates with the short-term evolution of the disease. Improvements in assistance based on the particularities of each hemodynamic profile are necessary to improve the outcomes of hospitalized patients and reduce readmissions.